Use of available engineering tools for modelling in multiple industries - Khaliev Magomed; Deunezhev Zalim; Dubovik Natalia (ITM Web of Conferences)
This paper explores the diverse applications of modern engineering tools across various industries, including agriculture, medicine, robotics, and education. The study examines popular software packages such as SolidWorks, Ansys, Abaqus, Fusion360, and Inventor, highlighting their specific capabilities and uses in different sectors. In agriculture, these tools are utilized for equipment design, structural analysis, and safety improvements in production systems. The medical field benefits from engineering software for instrument development, analysis of human body parts, and treatment planning. Robotics heavily relies on these tools for part design, assembly, mobility analysis, and simulation of various scenarios. The educational sector, while currently underutilizing these tools, shows potential for increased integration to foster innovation and practical skills among students. The paper also touches on the use of engineering tools in entertainment and hobbyist applications. Looking towards the future, the study predicts significant advancements in engineering tools, particularly with the integration of artificial intelligence. These developments are expected to enhance intuitive design, simplify analysis processes, and expand capabilities for handling complex structures. This comprehensive analysis demonstrates the widespread adoption and versatility of engineering tools across multiple industries, emphasizing their crucial role in technological advancement and innovation.